Implementation of Work-Life Balance and Work Stress for Job Satisfaction During the Covid-19 Pandemic - Butarbutar, Marisi; Lubis, Abdi Kurnia; Siregar, Robert Tua; Supitriyani, Supitriyani (Journal of Governance Risk Management Compliance and Sustainability, 2022)
In order to maximize work-life balance, minimize work stress, and utilize teachers as human resources, flexible work arrangements must be implemented. It is intended that the adoption of online learning platforms will lessen stress and boost job satisfaction by requiring teachers to practice work-life balance and flexible scheduling. But in practice, a lot of teachers do not even feel satisfied in their positions. This study aims to examine the relationship between work-life balance, stress at work, and job satisfaction as well as the impact of these factors on job satisfaction. This study focuses on the 168 State High School Civil Servants Teachers in Pematang Siantar City who received their certifications using a proportional random sample technique and normality-based data analysis. The SPSS Statistic version 20 program was used to run the test. The findings demonstrated that the answers met the criteria for job satisfaction, work-life balance, and work stress. The analysis of the correlation coefficient produced strong and favorable results. The results of the hypothesis testing revealed that, during the COVID 19 pandemic, Senior High School Teachers in Pematang Siantar City's work-life balance and work stress have a favorable and significant impact on job satisfaction.